ONLINE CLASSES: an experience enhanced by covid19 - Oliveira, Rosemary Lapa de (Revista Observatório, 2021)
This is a critical study of an experience of a post-doctoral professor, user and student of digital media, a teacher of distance education who is urged to continue with online classes after the confinement orientation because of COVID19. It is also a critical reflection on the paths of education in Brazil. The research is empirical and its research subject is the researcher herself who dialogues education with the state of mourning, due to the pandemic, thus seeking theoretical anchorage in psychology. In education, it dialogues with political, methodological and technology issues in education. This text points to the fact that education will have to change structurally and methodologically.